Distribution of heavy metals in soils and vegetables and health risk assessment in the vicinity of three contaminated sites in Guangdong Province, China. Issue 7 (3rd October 2018) - Zeng, Luping; Zhou, Fei; Zhang, Xuechun; Qin, Junhao; Li, Huashou
ABSTRACT: Due to rapid industrialization and urbanization, human activities like industrial and agricultural production, transportation, aggravate heavy metal pollution in soil and continue to endanger vegetables and human health. In this study, three contaminated areas affected by heavy metal pollution in Guangdong Province were investigated in terms of Cu, Zn, Pb, and Cd concentrations in soil and vegetables. Further analyses of the contamination status and potential risks to the health of residents consuming these vegetables were conducted. Results showed the following average heavy metal concentrations in vegetables and soil: Shaoguan > Guangzhou > Dongguan, indicating that mining has caused massive soil-heavy metal pollution. The heavy metal concentrations and Bioconcentration factors (BCFs) showed the following trend: leaf-vegetables > fruit-vegetables > root-vegetables, and those of vegetable type were as follows: Cd > Zn > Cu > Pb. The Nemero pollution index (PI) of all research region soils and hazard index (HI) exceeded 1. Hence, more attention should be paid to the potential for adverse health effects caused by the consumption of vegetables produced in these sites . Thus, effective measures are encouraged, with a focus on children due to their vulnerability to these heavy metals.